2015
DOI: 10.1080/15213269.2015.1006789
|View full text |Cite
|
Sign up to set email alerts
|

Can't See the Forest for the Trees? The Effect of Media Multitasking on Cognitive Processing Style

Abstract: Media multitasking represents an important aspect of the recent evolution in media consumption habits. While some experimental research exists, it has primarily focused on the detrimental effects of multitasking on task performance. We go a step further by examining the impact of media multitasking on information processing style. Study I demonstrates that media multitasking, compared to sequential media consumption, leads to a more local perceptual processing style. Furthermore, the frequency of media switchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 71 publications
0
9
0
3
Order By: Relevance
“…Accordingly, research by Ophir et al (2009) suggests that media multitasking may have detrimental effects on attention because it results in a reduced ability to ignore irrelevant information. Similarly, Kazakova, Cauberghe, Pandelaere, and de Pelsmacker (2015) have shown experimentally that a media multitasking situation leads to differences in processing style immediately following this situation.…”
mentioning
confidence: 83%
“…Accordingly, research by Ophir et al (2009) suggests that media multitasking may have detrimental effects on attention because it results in a reduced ability to ignore irrelevant information. Similarly, Kazakova, Cauberghe, Pandelaere, and de Pelsmacker (2015) have shown experimentally that a media multitasking situation leads to differences in processing style immediately following this situation.…”
mentioning
confidence: 83%
“…Panek (2012Panek ( , 2014 demonstrates that the immediate availability of many media choices unconsciously biases selection behavior and favors overuse. Research on computer multitasking has shown that having to switch between different frames and windows increases the perception of being overwhelmed by data and information and decreases cognitive performance (e.g., Kazakova, Cauberghe, Pandelaere, & De Pelsmacker, 2015;Ophir, Nass, & Wagner, 2009;Yeykelis, Cummings, & Reeves, 2014). Scholars have also investigated procrastination practices in the daily use of digital media as linked to excessive Internet use (Meier, Reinecke, & Meltzer, 2016;Reinecke et al, 2016).…”
Section: Internet Overuse As a Psychological And Social Problemmentioning
confidence: 99%
“…First, studies must have examined the association between measures of media multitasking and self-report measures of cognition, or psychological traits or mental-health issues related to cognition. Therefore, four review articles (Aagaard, 2015;Carrier, Rosen, Cheever, & Lim, 2015;Lin, 2009;van der Schuur et al, 2015), two meta-analysis (Jeong & Hwang, 2016; Wiradhany & Nieuwenstein, 2017), one measurement validity article (Baumgartner, Lemmens, Weeda, & Huizinga, 2017), 12 articles which only included laboratory task performance measures Alzahabi, Becker, & Hambrick, 2017;Cain & Mitroff, 2011;Edwards & Shin, 2017;Gorman & Green, 2016;Lui & Wong, 2012;Moisala et al, 2016;Murphy et al, 2017;Ophir et al, 2009;Ralph & Smilek, 2016;Ralph et al, 2015;Yap & Lim, 2013), two articles in which the level of media multitasking was manipulated (Kazakova, Cauberghe, Pandelaere, & De Pelsmacker, 2015;Lin, Robertson, & Lee, 2009), one article in which only a brain imaging measure was used (Loh & Kanai, 2014) and two articles in which only media multitasking behavior was observed (Loh, Tan, & Lim, 2016;Rigby, Brumby, Gould, & Cox, 2017) were excluded from further eligibility assessment.…”
Section: Study Selectionmentioning
confidence: 99%